Media, propaganda and politics in 20th-century Japan - Kushner, Barak 1968-; Funabashi, Yåoichi 1944- (SOAS studies in modern and contemporary Japan., 2015)
This book investigates the role played by the Asahi Newspaper, one of Japan's largest daily newspapers, as a mediator of information and power during the twentieth century. Members of staff at the paper, including Funabashi Yoichi, former Editor-in-Chief and one of the most trusted public intellectuals in Japan, examine the paper's role in Japanese history, showing how news agencies assisted in the creation and maintenance of the nation's goals, dreams, and delusions. The book draws on internal documents, committee meeting notes, and interviews with the staff at the company as a means to narrate what newspaper editors chose to publish during Japan's journey through the twentieth century. As well as offering an original insight into wartime media, [this book] explores the relationship between media and society during the postwar era and into the twenty-first century. -- Back cover.